2019
DOI: 10.1016/j.smr.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Australian women promoting health through sport

Abstract: Highlights There are health disparities between Indigenous and non-Indigenous Australians  Indigenous women are keen to seek support and opportunities which will serve to improve their health. Agency and empowerment will enable women to self-manage their health concerns  Partnerships between health agencies and sport organisations may improve these disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
(43 reference statements)
2
18
0
1
Order By: Relevance
“…Ultimately, 27 studies were included ( Figure 1 ). Three studies [ 29 , 30 , 31 ] were different analyses of the same data set and were grouped together for data extraction and presentation. Four studies were identified in grey literature [ 18 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, 27 studies were included ( Figure 1 ). Three studies [ 29 , 30 , 31 ] were different analyses of the same data set and were grouped together for data extraction and presentation. Four studies were identified in grey literature [ 18 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published between 2008 and 2020. The studies took place across all Australian states and territories, with six studies taking place across multiple states and territories [ 29 , 30 , 31 , 33 , 40 , 41 ]. Eight took place solely in Queensland (Qld) [ 32 , 36 , 42 , 43 , 44 , 45 , 46 , 47 ], two in Victoria [ 38 , 48 ], two in New South Wales (NSW) [ 49 , 50 ], three in the Northern Territory (NT) [ 18 , 35 , 51 ], three in Western Australia (WA) [ 34 , 37 , 52 ], one in South Australia (SA) [ 39 ], and one in Tasmania (Tas) [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of female athletes in "masculine" sports in the context of achievement is not only constrained by the problem of community view, which places them in a cultural context (2) but often associated with physiological problems (menstruation). During menstruation, many women experience various disorders that may interfere with their activities, which include physical disorders such as pain in joints and muscles, as well as psychological obstacles such as sensitivity and feelings of laziness.…”
Section: Introductionmentioning
confidence: 99%
“…Dentro de la gran oferta de deportes de aventura ligadas al turismo se encuentra al ciclismo, cuyo desarrollo es muy escaso dentro del turismo sostenible (Kruger et al, 2016), que se considera como un vector de desarrollo para los distintos actores que participan dentro de esta actividad (Gutiérrez, 2016), basado en tres aspectos fundamentales: uno ambiental, uno social y un económico (Gazzola et al, 2018). Las expectativas motivacionales de este tipo de turismo en orden de importancia son: compromiso frente a un evento, el estilo de vida, el logro y desafío, el escape y socialización, el prestigio internacional del evento y maestría en habilidades y afiliación grupal (Lacosta Aragüés, 2004), sin dejar de lado el importante aporte de experiencias placenteras que involucran disfrute y aprendizaje significativo (Chiu & Leng, 2017), contribuyendo a mejorar la salud mental y física del ser humano (Stronahc et al, 2018).…”
Section: Introductionunclassified